HUBUNGAN KELUHAN PASANGAN USIA SUBUR (PUS) DENGAN LAMA PEMAKAIAN KB INTRA UTERINE DEVICE (IUD) PADA AKSEPTOR AKTIF IUD DI DESA LAMCEU KUTA BARO ACEH BESAR TAHUN 2020 - Rahmayani Rahmayani; Sri Rosita; Deliana Deliana (Universitas Pahlawan Tuanku Tambusai, 2022)
In Aceh Province, the users of the IUD IUD are 12,659 (3.5%). From a report by the Aceh Besar Health Office, in 2019 the number of IUD contraceptive users was 3158 (129.11%). The low interest of users of IUD KB due to complaints of pain (pain), vaginal discharge and bleeding is one of the most important medical reasons an IUD acceptor decides to stop using it and it occurs 4-15% per year. The purpose of this study was to determine the Correlation between Complaints of Fertile Age Couples (PUS) and the Length of Intra-Uterine Device (IUD) KB for Active IUD Acceptors in Lamceu Village Kuta Baro Aceh Besar in 2020. This research is analytic with cross sectional design. The population and sample in this study were 90 people. The study was conducted in 27 Juni s/d 01 July 2020. Data were processed univariate and bivariate he results showed there is a relationship between changes in menstrual cycles (P value = 0.04), complaints of abdominal pain (P value = 0.005), vaginal discharge (0.04) and sexual relationship disorders (P value = 0.001) with the duration of KB intra-uterine device (IUD) On IUD Active Acceptors in Lamceu Village Kuta Baro Aceh Besar in 2020. It was expected that officers will establish a sustainable reproductive health education program, bearing in mind that there are still IUD acceptors who do not know clearly about complaints that might occur due to the use of an IUD. Health workers in this case serving family planning are expected to always provide education and information to prospective acceptors and acceptors of family planning IUDs about types of IUD contraception especially their advantages and disadvantages. Keywords: Duration of Use of IUD, PUS, Complaints IUD